Characterization of aggregates of five quarries of the province of Tacna and its optimization for use in construction works - Zavaleta Villanueva, Jesús Raúl (2020)
The characterization of the aggregates of the five main quarries of the province of Tacna that allows to optimize its use in construction works. Quantitative, explanatory and descriptive study where the physical properties of the aggregate were determined by performing the tests according to the parameters established in the Peruvian Technical Standard NTP 400.037. The mixing design was developed according to the ACI method for f'c-210 kg/cm2. Subsequently, nine concrete witnesses were made, for each of the following quarries; Arunta, Magollo, Arunta II, Jonas I and the proposal for exploitation located in the district of Sama, at ages 7, 14 and 28 days. When performing the compression test it was observed that the concrete made with the different aggregates complies with the parameters established by the Peruvian Technical Standard. The proposed quarry located in Sama district showed optimal conditions for the exploitation of aggregates, since when performing the compression test it obtained a resistance of 319.61 kg/cm2 to 28 days.